ELSI-COVID-19 initiative: methodology of the telephone survey on coronavirus in the Brazilian Longitudinal Study of Aging - Maria Fernanda Lima-Costa; James Macinko; Fabiola Bof de Andrade; Paulo Roberto Borges de Souza Júnior; Maurício Teixeira Leite de Vasconcellos; Cesar Messias de Oliveira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
The COVID-19 pandemic (caused by the SARS-CoV-2) is a public health emergency of international concern that particularly affects older people. Brazil is one of the countries most affected by the pandemic, ranking second with the highest number of confirmed cases and deaths worldwide as of mid-June 2020. The ELSI-COVID-19 initiative is based on telephone interviews with participants of the Brazilian Longitudinal Study of Aging (ELSI-Brazil), conducted on a nationally representative sample of the population aged 50 or older. This initiative aims to provide information on adherence to preventive measures (social distancing, wearing masks, and handwashing/hygiene); reasons for leaving the house, when that was the case; difficulties obtaining medications, medical diagnosis of COVID-19, and receipt of confirmatory results; use of health-care services (recent care-seeking, care-seeking location, care receipt, among other aspects); and mental health (sleep, depression, and loneliness). The first round of telephone interviews was conducted between May 26 and June 8, 2020. The second and third rounds are expected to occur within the coming months. This article presents this initiative methodology and some sociodemographic characteristics of the 6,149 participants in the survey first round, relative the Brazilian population within the same age group.